The Relationship of Learning Motivation With Student’s Academic Resilience - Aisyiah Aiwani; Ah. Fahri Munir (Universitas Negeri Malang, 2023)
This research aims to determine the picture of student learning motivation and academic resilience by looking for the relationship between the two. The subjects of this research are students who are studying at college. Basically, students are individuals who are trained and required to be able to solve their academic problems optimally. Judging from this, students need good academic resilience and maximum motivation to learn. Based on research conducted using a quantitative approach, the results showed that as many as 100 people who filled out the questionnaire obtained a significance value of 0.375, which means that learning motivation has a sufficient correlation with academic resilience. This is also because the source of an individual's resilience and strength arises first from within